The Mother-Daughter Book Club [large type] - Patterson, Susan, 1957-; Patterson, James, 1947- (Little, Brown and Company, 2026)
"Between their busy lives and their far-flung residences, the Mother-Daughter Book Club--four longtime college friends and their five daughters--more often discuss the books on their nightstands via 2 a.m. texts than in-person meetings. And maybe it's just as well, after what happened at their last get-together... So it's an emotional reunion when they finally gather again, this time on the spectacular shores of Italy's Lake Como. Sightseeing excursions, reminiscing fueled by "Como-politans," and a hint of vacation romance all build toward the book club's trademark "Night of Secrets." These friends, and sometimes rivals, are close readers--of novels, memoirs, and of each other. But as the years and the distance cast shadows and doubt, confidences and sympathies turn into surprising revelations." --